Inflation Forecasts Versus Shaping Inflation Expectations. Comparative Analysis - Magdalena Szyszko (Comparative Economic Research, 2015)
This article jointly analyzes inflation expectations of consumers and inflation forecasts. Its starting point is the predominant role of expectations in monetary policy. This is crucial market information in the decision-making process of the central bankers as it may show the actual future inflation. On the other hand, the central bank wants to influence expectations in order to facilitate achieving the main goals of monetary policy. Inflation forecasting is a tool for shaping public expectations. In the research, covering four central banks (the National Bank of Hungary, National Bank of Poland, the Czech National Bank, Sveriges Riksbank), the author analyzes the interdependencies of inflation forecasts and inflation expectations of consumers. Data on expectations are derived from the surveys and quantified. Then non-parametric measures of association are calculated. The results confirm the hypothesis on the existence of such relationships. The strength of this interdependence varies among countries, from weak to strong. The study opens the field for further discussions on strengthening this relationship.